A modified DMBE IV Potential with spectroscopic accuracy: vibrational levels and rotational constants - Rio, Carolina (2015)
The corrected DMBE IV potential, here named DMBE IV-C, accurately reproduces the vibrational levels (errors < 0.01 cm-1) and rotational constants, while keeping constant the remaining features of this PES that should control the reaction dynamics.